Influence of Heat Treatment on the Microstructure and Composition of Plasma Sprayed Coatings - Zorawski, Wojciech; Chatys, Rafal (Communications - Scientific letters of the University of Zilina, 2004)
Plasma sprayed coatings have been used in various industries for a number of purposes. To increase their mechanical properties, different methods of thermal treatment are being applied. This work is concerned with composite coatings obtained by plasma spraying of the Al2O33TiO2 and NiO powders (50 % and 50 % by weight), which were then reduced at an atmosphere of dissociated ammonia. Their chemical composition and morphology were determined by means of the EDS microprobe and the Joel 5400 scanning microscope respectively. It has been reported that the process of reduction contributes to the homogeneity of the coating, and that the modified structure contains Al2O3 and Ni.